Vascular Coupling in Resting-State FMRI: Evidence from Multiple Modalities. Issue 12 (December 2015) - Zhu, David C; Tarumi, Takashi; Khan, Muhammad Ayaz; Zhang, Rong
Resting-state functional magnetic resonance imaging (rs-fMRI) provides a potential to understand intrinsic brain functional connectivity. However, vascular effects in rs-fMRI are still not fully understood. Through multiple modalities, we showed marked vascular signal fluctuations and high-level coupling among arterial pressure, cerebral blood flow (CBF) velocity and brain tissue oxygenation at < 0.08 Hz. These similar spectral power distributions were also observed in blood oxygen level-dependent (BOLD) signals obtained from six representative regions of interest (ROIs). After applying brain global, white-matter, cerebrospinal fluid (CSF) mean signal regressions and low-pass filtering (< 0.08 Hz), the spectral power of BOLD signal was reduced by 55.6% to 64.9% in all ROIs ( P = 0.011 to 0.001). The coherence of BOLD signal fluctuations between an ROI pair within a same brain network was reduced by 9.9% to 20.0% ( P = 0.004 to < 0.001), but a larger reduction of 22.5% to 37.3% ( P = 0.032 to < 0.001) for one not in a same network. Global signal regression overall had the largest impact in reducing spectral power (by 52.2% to 61.7%) and coherence, relative to the other three preprocessing steps. Collectively, these findings raise a critical question of whether a large portion of rs-fMRI signals can be attributed to the vascular effects produced from upstream changes in cerebral hemodynamics.